A Micromolding Method for Transparent and Flexible Thin‐Film Supercapacitors and Hybrid Supercapacitors. (9th September 2020) - Liu, Tian; Yan, Runyu; Huang, Haijian; Pan, Long; Cao, Xiaobao; deMello, Andrew; Niederberger, Markus
Abstract: Thin‐film supercapacitors are promising candidates for energy storage in wearable electronics due to their mechanical flexibility, high power density, long cycling life, and fast‐charging capability. In addition to all of these features, device transparency would open up completely new opportunities in wearable devices, virtual reality or in heads‐up displays for vehicle navigation. Here a method is introduced for micromolding Ag/porous carbon and Ag/Ni x Fe y O z @reduced graphene oxide (rGO) into grid‐like patterns on polyethylene terephthalate foils to produce transparent thin‐film supercapacitors and hybrid supercapacitors. The supercapacitor delivers a high areal capacitance of 226.8 µF cm −2 at a current density of 3 µA cm −2 and with a transparency of 70.6%. The cycling stability is preserved even after 1000 cycles under intense bending. A hybrid supercapacitor is additionally fabricated by integrating two electrodes of Ag/porous carbon and Ag/Ni x Fe y O z @rGO. It offers an areal capacitance of 282.1 µF cm −2 at a current density of 3 µA cm −2, a transparency of 73.3% and the areal capacitance only decreases slightly under bending. This work indicates that micromolding of nano‐ and micro‐sized powders represents a powerful method for preparing regular electrode patterns, which are fundamental for the development of transparent energy storage devices. Abstract : Transparent and flexible thin‐film supercapacitors and hybrid supercapacitors are prepared by micromolding Ag/porous carbon||Ag/porous carbon and Ag/porous carbon||Ag/Ni x Fe y O z @rGO electrodes on polyethylene terephthalate foils, resulting in energy storage devices with high transparency, fast‐charging capability, long cycling life, and good electrochemical performance under harsh bending conditions.